Community treatment of latent tuberculosis in child and adult refugee populations: outcomes and successes - Harwood-Johnson, Emily; Leis, Karen S.; Hanson, Jacelyn; Olfert, Jordan; Blonde, Yvonne; Brindamour, Mahli (Frontiers in Public Health, 2023)
Background Tuberculosis (TB) is the world’s leading infectious cause of death, killing millions every year. In Canada, considered a low-incidence country for TB, the burden of the disease is unequally distributed, with most cases of latent tuberculosis infection (LTBI) experienced by newcomers from endemic regions. The purpose of this study was to measure LTBI treatment acceptance and completion outcomes of LTBI treatment at the REACH clinic in Saskatoon, a local refugee clinic providing primary care-based LTBI management. Methods A retrospective case series by sampling methodology was applied to review patients who visited the REACH clinic between January 2017 and June 2021 and who had an interferon-gamma release assay (IGRA) or tuberculin skin test (TST) done for LTBI screening. Those with positive results were retained for analysis. The LTBI treatment acceptance and completion groups were compared according to demographic variables, WHO regions of origin, year of arrival to Canada, and LTBI treatment regimen. Results A total of 523 patients were screened for LTBI, of whom 125 tested positive, leading to a test positivity of 23.9%. The treatment acceptance rate was 84.8%, and the treatment completion rate was 93.3%. All of those who declined treatment were more than 18 years of age (p = 0.02). Otherwise, treatment acceptance and completion rates did not vary significantly in association with gender, categories of refugees, WHO region of origin, year of arrival to Canada, or LTBI treatment regimen used. Discussion The refugee clinic acceptance and completion rates in this study are high and meet Canadian TB standards of care. The multidisciplinary clinic model and community support are important facilitators, which, in combination with shorter treatment regimens, offer a path forward for LTBI management among refugees resettling in low-incidence countries.